1988
DOI: 10.1038/sc.1988.6
|View full text |Cite
|
Sign up to set email alerts
|

A clinical review of the adult hip guidance orthosis (ParaWalker) in traumatic paraplegics

Abstract: SummaryTwenty Adult traumatic paraplegics with neurologically complete lesions between C8 and T12 have ambulated using a ParaWalker (adult hip guidance orthosis), for a minimum of 6 months at home. At follow up, on average 20 months from the date of issue of the orthosis, 17 patients (85%) were still regularly using their Para Walker. Patients achieved independent use of the orthosis and low energy ambulation both indoors and outdoors on a variety of surfaces.A new classification of adult paraplegic ambulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…This high score is comparable to the ®rst follow-up study on the HGO. 14 In that article, the remark was made that this number was probably so high because these users were highly motivated pioneers'. Indeed, in a second follow-up study at the same centre, 4 the number had dropped to 64%.…”
Section: Discussionmentioning
confidence: 99%
“…This high score is comparable to the ®rst follow-up study on the HGO. 14 In that article, the remark was made that this number was probably so high because these users were highly motivated pioneers'. Indeed, in a second follow-up study at the same centre, 4 the number had dropped to 64%.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated pattern of maintained usage by adult SCI individuals in the Walkabout orthosis, with a typical frequency of use between 1 ± 3 times per week and total duration of usage between 2 ± 3 hours per week, compares favourably with data previously published for the HGO. 9 Longer term follow-up will be required Figure 3 The Walkabout orthosis with corset attachment straps reversed and forearm crutches to monitor continued usage. Not surprisingly, orthotic ambulatory ability and con®dence were generally better in those where proprioception was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although orthoses have enabled some individuals to overcome architectural barriers such as stairs or narrow doorways, 5 in practice most patients have found that the necessary accompanying walking aids interfere with task performance and that the wheelchair is more e cient for mobility. 9,10 Even so, a large proportion of paraplegic individuals still desire improved mobility to overcome the problems of inaccessibility. 11 In contrast to an earlier study reporting that braces prescribed during rehabilitation are frequently later abandoned, particularly in patients with a neurological lesion above T12, 12 several authors have now reported an encouraging trend towards continued long-term usage of orthoses for exercise with patients describing strong feelings of physical and psychological well-being associated with their use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con trary to the previous experience of orthotic paraplegic walking, a recent survey (Summers et al, 1986) showed that 85() () of the patients were still regularly using their Para Walker at follow-up, on average 20 months from the date of supply of their orthosis. They all had a complete traumatic spinal cord injury between C8 and T12.…”
Section: Introductionmentioning
confidence: 99%